THE APPLICATION OF HANDOUT-ASSISTED ON JIGSAW COOPERATIVE LEARNING MODEL TO THE SCIENCE COMPETENCE OF 8th GRADER - Sari, Ulfa Junia; Zahra, Firda Az (Department of Science Education, 2024)
This study aims to determine the effect of the application of the handout-assisted jigsaw cooperative learning model on the science competence of 8th grader students at SMPN 1 BAYANG. This research is a quasi-experimental research. The research design was a nonequivalent posttest-only control group design. The population in this study were all students of 8th grader SMPN 1 Bayang. The sample from this study was taken by purposive sampling technique. In this study, data collection was carried out by filling out an observation questionnaire. The instrument used for knowledge competence is multiple choice and the instrument for skills competency is an assessment sheet. The results of data analysis on the posttest of the human respiratory system obtained tcount = 2.02 and ttable = 2.01. Meanwhile, in the posttest of the human excretory system, tcount = 2.04 and ttable = 2.01. For human respiratory system skills, tcount=2.02 and ttable=2.01. While the skills of the human excretory system obtained tcount 2.16 and ttable = 2.01. Because tcount > ttable with α=0.05 then Ho is rejected and Ha is accepted, which means that there is an influence or an increase in the achievement of science competence for class VIII students at SMPN 1 Bayang with the help of handouts.